“The Night Power” by Mohammad Firdaus Ibrahim: interpreting Islamic aesthetics through Imam Al-Ghazali's The Concept of Beauty Theory and The Nazariyyah Philosophy - Kamarudin Azhar, Muhamad Baha’uddin Imran; Manan, Juliana; Mokhtar, Mumtaz; Mohd Razis, Siti Nur Izaura (College of Creative Arts, 2025)
This study examined a piece of art called "The Night Power," which was made by Muhammad Firdaus Ibrahim, a Malaysian artist from Kedah. "Subhanallahi Wa Bihamdihi, Subhanallahi Azhim," one of the most well-known Dhikr in Islam, is used in this Islamic calligraphy painting. Muslims use this Dhikr as a recital to express their devotion to God. An interview with the artist was undertaken in order to gain a deeper understanding of the visual narratives surrounding this piece of art. Imam Al-Ghazali's The Concept of Beauty Theory and The Nazariyyah Philosophy will be used to analyse this piece of art in order to comprehend and decipher not only its aesthetic elements and tenets but also its spiritual narratives. The Night Power was similarly analysed, concluding that it achieved the highest level of beauty by representing the concept of loving Allah, who embodies love and beauty, while also reflecting the Nazariyyah philosophy within the painting.